Improved dynamic compensation for accurate cutting force measurements in milling applications. (March 2015) - Scippa, A.; Sallese, L.; Grossi, N.; Campatelli, G.
Abstract: Accurate cutting-force measurements appear to be the key information in most of the machining related studies as they are fundamental in understanding the cutting processes, optimizing the cutting operations and evaluating the presence of instabilities that could affect the effectiveness of cutting processes. A variety of specifically designed transducers are commercially available nowadays and many different approaches in measuring cutting forces are presented in literature. The available transducers, though, express some limitations since they are conditioned by the vibration of the surrounding system and by the transducer׳s natural frequency. These parameters can drastically affect the measurement accuracy in some cases; hence an effective and accurate tool is required to compensate those dynamically induced errors in cutting force measurements. This work is aimed at developing and testing a compensation technique based on Kalman filter estimator. Two different approaches named "band-fitting" and "parallel elaboration" methods, have been developed to extend applications of this compensation technique, especially for milling purpose. The compensation filter has been designed upon the experimentally identified system׳s dynamic and its accuracy and effectiveness has been evaluated by numerical and experimental tests. Finally its specific application in cutting force measurements compensation is described. Highlights: Cutting force measurements can be drastically affected by machine tool dynamics. Dynamic compensation can extend the bandwidth of commercial dynamometers. Two different approaches suitable for milling applications have been developed. The effectiveness of the proposed approaches has been experimentally evaluated. Examples in cutting force measurements compensation are shown.